Construction of a mavs-inactivated MDCK cell line for facilitating the propagation of canine distemper virus (CDV). (October 2019) - Cai, Cong; Wang, Xiaoping; Zhao, Ya; Yi, Chenyang; Jin, Zehua; Zhang, Anding; Han, Li
Highlights: The constructed MDCK-KO mavs is beneficial for the isolation of field CDVs. The propagation of a filed CDV strain was approximately 100 times higher in the MDCK-KO mavs cell line. The MDCK-KO mavs cell could be an alternative cell line for the preparation of vaccine antigens. Abstract: Canine distemper is a highly contagious disease of wild and domestic carnivores. Obtaining of a suitable cell line for canine distemper virus (CDV) propagation is very important for field CDV isolation and vaccine antigen preparation. However, the cell line currently developed cell lines for CDV propagation are a marmoset lymphoid cell line (B95a), which could cause the virus to potentially infect human cells, and canine SLAM-expressing Vero cells, which may cause the virus to lose virulence. Therefore, a canine cell line constructed for efficient CDV propagation would be attractive. In the present study, a Madin-Darby Canine Kidney Epithelial (MDCK) cell line with mavs (mitochondrial antiviral signaling) inactivation was constructed by CRISPR/Cas9 technology. The interferon-I response induced by poly(I:C), an analogue of viral RNA, was significantly blocked in the constructed cell line, designated MDCK-KO mavs . Moreover, the propagation of a filed CDV strain was approximately 100 times higher in MDCK-KO mavs cells than in wild-type MDCK cells. Therefore, in the present study, a canine cell line facilitating CDV propagation was successfully constructed, and the results suggested that the constructed canine cell line was more efficient than the wild-type cell line for the isolation of field CDVs. In addition, the rapid propagation of CDVs to high titers in the constructed MDCK-KO mavs cell line indicated that this cell line could also be an alternative cell line for the preparation of vaccine antigens.